A study of spatial and temporal distribution of land utilization pattern in Mopka village using RS & GIS (International Journal of Agricultural Research, Innovation and Technology, 2015)
Remote Sensing and GIS is a very good modality for retrospection and the strategy for better exploitation of sustainable land use system. The present study was conducted in the Bilaspur district for analyzing the spatial distribution of Land Use Change. During last decades the increasing population of Bilaspur city, affect the land use pattern of Mopka Village. The anthropogenic activities were affecting the agricultural land along with barren land. For the development of civic amenities the land of the above village was used. The main objective of the present study is to analyses the land use/land cover distribution in Mopka village, Bilaspur district in between last 12 years and to identify the main forces behind the changes. The objectives of present studies are, to create a land use land cover maps of Mopka village using satellite imagery. To analysis the temporal changes of village area in between the year 2000 and 2012, the primary, secondary and satellite data were used. The results of the present study show that the decadeial changes due to population growth and increasing demand of infrastructure were destroying the natural resources, natural habitat and soil structure of area.Int. J. Agril. Res. Innov. & Tech. 5 (1): 1-9, June, 2015